Identifying core elements in investment agreements in the APEC region (UN New YorkUS, 2008)
Identifies common, core elements of APEC international investment agreements and the way these provisions assist in the liberalization, protection and promotion of investment. Considers also how the core elements compare with investment principles of existing APEC instruments.
Keywords: INVESTMENT